Estudo comparativo de métodos para a determinação da concentração de carbono em solos com altos teores de Fe (Latossolos) - Segnini, Aline; Santos, Larissa Macedo dos; Silva, Wilson Tadeu Lopes da; Martin-Neto, Ladislau; Borato, Carlos Eduardo; Melo, Wanderley José de [UNESP]; Bolonhezi, Denizart (Sociedade Brasileira de Química, 2008)
Soil organic matter (SOM) plays an important role in physical, chemical and biological properties of soil. Therefore, the amount of SOM is important for soil management for sustainable agriculture. The objective of this work was to evaluate the amount of SOM in oxisols by different methods and compare them, using principal component analysis, regarding their limitations. The methods used in this work were Walkley-Black, elemental analysis, total organic carbon (TOC) and thermogravimetry. According to our results, TOC and elemental analysis were the most satisfactory methods for carbon quantification, due to their better accuracy and reproducibility.
Comparative study of carbon quantification methods in soil with high Fe contents (Oxisols)
Keywords: soil organic matter; carbon quantification methods; statistical evaluation